Electrocatalytic performances of N-doped graphene with anchored iridium species in oxygen reduction reaction. (25th September 2015) - Choi, Kwangrok; Lee, Seungjun; Shim, Yeonjun; Oh, Junghoon; Kim, Sujin; Park, Sungjin
Abstract: Development of new systems with high catalytic performances in the oxygen reduction reaction (ORR) for practical applications in fuel cells and metal–air batteries is a challenge. We develop a one-pot solution method for producing a novel hybrid material consisting of Ir species anchored on N-doped graphene. The hybrid is synthesized by reacting graphene oxide with IrCl3 · x H2 O in dimethylformamide under reflux. Chemical and structural analyses confirm the attachment of Ir atoms to the N and O atoms of the N-doped graphene-based materials. The hybrid shows a good electrocatalytic performance for the ORR in alkaline media, with an onset potential of 0.88 V (versus the reversible hydrogen electrode), high long-term durability, and good tolerance for methanol poisoning.